2000
DOI: 10.1017/s135772980005517x
|View full text |Cite
|
Sign up to set email alerts
|

Monthly variations in some reproductive parameters of Barki and Awassi rams throughout 1 year under subtropical conditions 2. Biochemical and enzymatic properties of seminal plasma

Abstract: Fifteen sexually mature rams, five each of Barki, Awassi (I, imported from Syria) and Awassi (LB, locally born in Egypt) were used to study the biochemical and enzymatic properties of seminal plasma for 12 months. The biochemical analyses of ram seminal plasma indicated that the highest values of total protein, albumin (A), globulin (G), fructose, total lipids and cholesterol were recorded in late summer and early autumn, while A/G and AST/ALT ratios exhibited the lowest values. Lowest values of the same param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Similarly, El-Nagar (2017) found the highest conception rate of Friesian cows artificially inseminated with semen extended with MOLE as compared to Tris egg-yolk. Such results were supported by the theory that, good quality of semen was characterized by lower AST, ALT and LDH of enzyme activity (Taha et al, 2000;Borah et al, 2015, El-Nagar, 2017. Generally, reducing activity of enzyme in seminal plasma of thawed semen is an indicator of membrane integrity, and subsequently sperm motility (El-Harairy et al, 2011)…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, El-Nagar (2017) found the highest conception rate of Friesian cows artificially inseminated with semen extended with MOLE as compared to Tris egg-yolk. Such results were supported by the theory that, good quality of semen was characterized by lower AST, ALT and LDH of enzyme activity (Taha et al, 2000;Borah et al, 2015, El-Nagar, 2017. Generally, reducing activity of enzyme in seminal plasma of thawed semen is an indicator of membrane integrity, and subsequently sperm motility (El-Harairy et al, 2011)…”
Section: Discussionmentioning
confidence: 79%
“…A glycerol complex, glyceryl‐phosphorylcholine was reported in SP (Dawson et al, 1956), and it was hypothesized that glyceryl‐phosphorylcholine might be an important source of energy for spermatozoa in the female reproductive tract (White and Wallace, 1961). Studies with ram semen have indicated that reduced sperm concentration and motility are associated with decreased SP lipid content (Taha et al, 2000). Total lipids and phospholipids have been quantified in alpaca SP (Garnica et al, 1993).…”
Section: Biochemical Constituents Of Sp and Their Functionsmentioning
confidence: 99%
“…Improving incidence of acrosomal damage in the present study was associated with the lower activity of AST, ALT and LDH due to CoQ10 enrichment to extender of both species, being better for buffalo than cattle semen. Such results were supported by the theory that, good quality of semen characterized by lower activity of AST, ALT and LDH enzymes (Taha et al, 2000;El-Harairy et al, 2011), that could be due to lower injuries inflicted to cell membrane as evidenced by significantly lower total incidence of acrosomal changes (Borah et al 2015).…”
Section: Discussionmentioning
confidence: 64%